Preparing presentations: practicalities and professionalism. (2nd May 2019) - Bernstein, Adam
Abstract : Giving a presentation is not a favoured activity for many people, but the right preparation can make all the difference. Adam Bernstein gives some practical advice on how to make the best of the experience for both presenter and audience.